1990
DOI: 10.1021/ma00217a008
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution solid-state carbon-13 nuclear magnetic resonance study of chitin

Abstract: as a consequence of small errors in the measurements of (/ii2) /nm2 that can affect in a significant way the value of the temperature coefficient. References and Notes(1) Flory, P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
88
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(102 citation statements)
references
References 19 publications
(20 reference statements)
12
88
0
2
Order By: Relevance
“…Higher heating temperatures gave sharp carbon signals assigned as chitin signals, C 1 (104.8 ppm), C 2 (57.4 ppm), C 3 (75.4 ppm), C 4 (84.4 ppm), C 5 (77.0 ppm), C 6 (60.6 ppm), C=O (173.6 ppm) and CH3 (24.6 ppm), characteristic of crab chitin. 25) Signals became sharper with the increase in heating temperature in accordance with the FT IR spectroscopic analyses. These results indicate that most of the chitin, unlike other constituents, could not be dissolved in water even at 230 C. Based on the results presented above, it was suggested that the water insoluble components remaining after microwave irradiation at temperatures of above 210 C were dominantly composed of chitin.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Higher heating temperatures gave sharp carbon signals assigned as chitin signals, C 1 (104.8 ppm), C 2 (57.4 ppm), C 3 (75.4 ppm), C 4 (84.4 ppm), C 5 (77.0 ppm), C 6 (60.6 ppm), C=O (173.6 ppm) and CH3 (24.6 ppm), characteristic of crab chitin. 25) Signals became sharper with the increase in heating temperature in accordance with the FT IR spectroscopic analyses. These results indicate that most of the chitin, unlike other constituents, could not be dissolved in water even at 230 C. Based on the results presented above, it was suggested that the water insoluble components remaining after microwave irradiation at temperatures of above 210 C were dominantly composed of chitin.…”
Section: Resultssupporting
confidence: 80%
“…1. gel by β glucan. Based on the results of the analysis of the water insoluble components by solid state 13 C CP MAS NMR, it was found that longer irradiation time gave sharp carbon signals characteristic of crab chitin 25) ( Fig. 6), similar to the results obtained by microwave assisted extraction at 180 C for 5 min.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…2): spectrum a, which corresponds to cell walls analyzed under dry conditions, shows two small resonances at 174 and 23.6 ppm (arrows 1 and 2) that are also observed when crystalline crab shell chitin is analyzed either under dry or wet conditions (spectrum b). These resonances can be ascribed to the CAO and the CH 3 moieties of N-acetyl-D-glucosamine (77). Similar resonances were also observed in Aspergillus niger and ascribed to chitinaceous compounds in interaction with glucans by CP-MAS NMR (42).…”
Section: Vol 7 2008 Aphanomyces Euteiches Cell Wall Chitosaccharidesupporting
confidence: 72%